Atomic Habits :An easy and Proven Way to Build Good Habits and Break Bad Ones - James Clear (Cornerstone Press London, 2018)
World-renowned habits expert James Clear has discovered a simpler system for transforming your life. He knows that lasting change comes from the compound effect of hundreds of small decisions doing two push-ups a day, waking up five minutes early, or holding a single short phone call. He calls them atomic habits. In this ground-breaking book, Clear reveals how these tiny changes will help you get 1 percent better every day. He uncovers a handful of simple life hacks (the forgotten art of Habit Stacking, the unexpected power of the Two Minute Rule, or the trick to entering the Goldilocks Zone) and delves into cutting-edge psychology and neuroscience to explain why they matter. Along the way, he tells inspiring stories of Olympic gold medalists, leading CEOs and distinguished scientists who have used the science of small habits to stay productive, motivated and happy. These small changes will have a revolutionary effect on your career, your relationships and your life...................
Keywords: GEN